The Impact of Social Responsibility on Emotional and Behavioral Responses of Tourists After Failure in Four-Five-Star Hotels (Case Study: Tehran City) - sara dodange; babak hajikarimi; MOHAMMAD mehdi mozafri; kamiar kavosh (تحقیقات کاربردی علوم جغرافیایی)
The purpose of present study was to investigate the effect of social responsibility on emotional and behavioral responses of tourists after failure of services in four-star and five-star hotels. The research method is practical  obgectively and descriptive and analytical methodology. The statistical population of the study was contained tourists who visited four-star and five-star hotels, and the sample size was estimated 384 people by the Cochran formula, sampling method was simple random. The data gathering tool was the questionnaire whose validity and reliability were confirmed. For investigating and testing of the research hypotheses was used structural equation modeling in the software environment, pls. The results of the research indicated that social responsibility has a positive and significant effect on loyalty, satisfaction and trust of tourists. In addition, findings showed that the satisfaction and trust of tourists have a positive and significant effect on their loyalty.